2015
DOI: 10.1007/s12043-015-1005-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanostructure composite for electromagnetic interference shielding

Abstract: This communication reviews current developments in carbon nanostructure-based composite materials for electromagnetic interference (EMI) shielding. With more and more electronic gadgets being used at different frequencies, there is a need for shielding them from one another to avoid interference. Conventionally, metal-based shielding materials have been used. But due to the requirement of light weight, corrosion resistive materials, lot of work is being done on composite materials. In this research the forerun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 130 publications
1
55
0
1
Order By: Relevance
“…They confirmed that adding magnetic iron oxide particles improved the magnetic shielding effect of composite material fabricated. Joshi et al [9] studied the effect of adding carbon nanostructure into epoxy resin composite. They confirmed that addition of carbon nanostructure increased the conductivity of epoxy resin and attenuate the microwaves.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that adding magnetic iron oxide particles improved the magnetic shielding effect of composite material fabricated. Joshi et al [9] studied the effect of adding carbon nanostructure into epoxy resin composite. They confirmed that addition of carbon nanostructure increased the conductivity of epoxy resin and attenuate the microwaves.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are widely used in radar applications, for solving problems of increased electromagnetic environment pollution (via design of electromagnetic compatibility (EMC) materials and components), metamaterials, etc. Nanomaterials based on different forms of carbon (carbon black, activated carbon, carbon fibers, nanotubes, graphene) are the most important components in the development of EMM due to the successful combination of their properties (electrical conductivity, chemical stability, and lightness) . Among these materials, aerogels of multiwalled carbon nanotubes (MWCNTs) combine the unique mechanical, thermal, and electrical properties of nanotubes with specific characteristics of aerogels (low density, high porosity, and large surface area) .…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials based on different forms of carbon (carbon black, activated carbon, carbon fibers, nanotubes, graphene) are the most important components in the development of EMM due to the successful combination of their properties (electrical conductivity, chemical stability, and lightness). [6][7][8][9][10] Among these materials, aerogels of multiwalled carbon nanotubes (MWCNTs) combine the unique mechanical, thermal, and electrical properties of nanotubes with specific characteristics of aerogels (low density, high porosity, and large surface area). [11] Due to the absence of a binder polymer, aerogels have the lowest density combined with high conductivity, which are unattainable for other classes of composites.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Recently, considerable amount of papers have reported that the graphene/polymer composite possesses enhanced barrier properties that are beneficial for high anticorrosion performances. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Unlike carbon nanotubes that can only provide similar mechanical benefits, [10] these lightweight sheets can reduce oxygen permeability of host membranes. [15,31] It also should be noted that the graphene process outstanding electrical conductivity, [32][33][34] which can increase the conductivity of coatings when doped into the polymer matrixes.…”
Section: Introductionmentioning
confidence: 99%